APPLICATION OF DATA MINING TO DETERMINE PRODUCT ADMINISTRATION USING APRIORI ALGORITHM - Zunita Wulansari (Universitas Islam Balitar, 2019)
Product Arrangement is a way of arranging products to attract consumers. Product arrangement is also known as display. But in fact there are still many entrepreneurs who have not paid attention to the arrangement of their products. So that many consumers are not interested in buying products because the arrangement is less attractive which makes the company's income does not increase. Therefore researchers have a solution to solve the problems that exist in the shop. That is, with the application of data mining to determine the arrangement of products using a priori algorithm, the results can be used as a company guide to determine the display of goods and as a guide to promote goods that are less sold to participate or sell quickly. Based on the results of the trials that have been carried out, it is known that the a priori algorithm is used to help determine the product structuring solution from the sales data of Warung Sayur Segar products so that it can later be used as a consideration in determining an effective structuring and sales strategy.